2021
DOI: 10.1136/bmjopen-2021-049837
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide seroprevalence of antibodies to SARS-CoV-2 in asymptomatic population in South Korea: a cross-sectional study

Abstract: ObjectiveAsymptomatic active infection might be an important contributor to the COVID-19 outbreak. Serological tests can assess the extent of exposure and herd immunity to COVID-19 in general populations. This study aimed to estimate the nationwide seroprevalence of SARS-CoV-2 antibodies according to age, sex and clinical status in South Korea.Design, setting and participantsThis cross-sectional study randomly selected health examinees who underwent health check-up at 16 health promotion centres in 13 Korean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Finally, the current survey population was composed of people in which blood test was prescribed for medical reasons (e.g., chronic diseases), they could have been more careful and decreased their exposure to the virus, which resulted in an underestimation of seroprevalence so they may not reliably represent the whole Corsican population. However, there is no evidence to suggest a greater susceptibility to COVID-19 in people undergoing blood tests in clinical laboratories and several nationwide studies have employed this biological sample (“residual sera”) to describe SARS-CoV-2 circulation ( 2 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current survey population was composed of people in which blood test was prescribed for medical reasons (e.g., chronic diseases), they could have been more careful and decreased their exposure to the virus, which resulted in an underestimation of seroprevalence so they may not reliably represent the whole Corsican population. However, there is no evidence to suggest a greater susceptibility to COVID-19 in people undergoing blood tests in clinical laboratories and several nationwide studies have employed this biological sample (“residual sera”) to describe SARS-CoV-2 circulation ( 2 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found that patients with obesity have higher anti‐SARS‐CoV‐2 levels than lean patients 82,84–86 (Figures 2 and 3). However, other studies showed that seroprevalence against SARS‐CoV‐2 did not differ with BMI or any biochemical parameters 78,83 …”
Section: Resultsmentioning
confidence: 93%
“…However, other studies showed that seroprevalence against SARS‐CoV‐2 did not differ with BMI or any biochemical parameters. 78 , 83 …”
Section: Resultsmentioning
confidence: 99%
“…In Korea, since early in the pandemic, there has not been a shortage of COVID-19 tests, so even asymptomatic patients could freely be tested by PCR with contact tracing or voluntary testing. Consequently, undiagnosed COIVD-19 infections seem to be very rare according to a seroprevalence study in Korea [38]. In addition, all the COVID-19 patients stayed in residential treatment centers or hospitals until recovery or death and were treated without charge.…”
Section: Discussionmentioning
confidence: 99%